2002
DOI: 10.1002/zoo.10042
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of environmental enrichment on harbor seals (Phoca vitulina concolor) and gray seals (Halichoerus grypus)

Abstract: Zoos and aquariums have been incorporating environmental enrichment into their animal care programs for the past 30 years to increase mental stimulation and promote natural behaviors. However, most attempts to document the effects of enrichment on animal behavior have focused on terrestrial mammals. Staff at the National Aquarium in Baltimore conducted an investigation of the behavioral effects of enrichment on the seven harbor seals and two gray seals housed in the aquarium's outdoor seal exhibit. We expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 12 publications
6
35
0
2
Order By: Relevance
“…Test on salmonids showed that exposure to such conditions increases the ability of fish to feed on novel prey (Brown et al 2003) and increased survival after restocking in semi-natural conditions (Maynard et al 1996). These results could be explained by the improvement of cognitive efficiency and behavioral flexibility as proven in other reintroduced animal groups (Hunter et al 2002;Rabin 2003).…”
Section: Introductionmentioning
confidence: 77%
“…Test on salmonids showed that exposure to such conditions increases the ability of fish to feed on novel prey (Brown et al 2003) and increased survival after restocking in semi-natural conditions (Maynard et al 1996). These results could be explained by the improvement of cognitive efficiency and behavioral flexibility as proven in other reintroduced animal groups (Hunter et al 2002;Rabin 2003).…”
Section: Introductionmentioning
confidence: 77%
“…Animal development and the evolution of behaviour patterns, morphology and life-history traits are also strongly influenced by the environment (Magurran 2005). In mammals and birds, complex environments stimulate the development of neural tissue, cognitive performance and flexible behaviour (Hunter et al 2002, Kempermann et al 2002, Bredy et al 2003, Rabin 2003. For example, food storing birds have a larger hippocampus than non-storing birds (Clayton & Krebs 1994), and more diverse behaviour and better stress responses are promoted in rodents when they experience environmental complexity (Sackett et al 1999, Harris et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Work with other captive vertebrates such as birds and mammals has already illustrated how increasing environmental complexity, sometimes referred to as environmental enrichment, can increase behavioural and neuronal plasticity, improve cognitive performance and increase survival in reintroduced species (Hunter et al 2002;Kempermann et al 2002;Bredy et al 2003;Rabin 2003). Similarly, with fishes, resource predictability and distribution can influence behaviour and social interactions (McLaughlin et al 1992;Grand & Grant 1994;Ryer & Olla 1996.…”
Section: Introductionmentioning
confidence: 99%